Institutional authority and collusion: experimental data - Sonntag, Axel (UK Data Service, 2015)
This data is the result of a decision-making experiment, showing that, if managers are deferential towards an authority, firms can induce more collusion by delegating production decisions to middle managers and providing suitable informal nudges. This holds not only with two but also with four firms. We are also able to distinguish compliance effects from coordination effects. A ‘collusion puzzle’ exists by which, even though increasing the number of firms reduces the ability to tacitly collude, and leads to a collapse in collusion in experimental markets with four or more firms, in natural markets there are such numbers of firms colluding successfully. This data stems from a lab experiment and contains in total 8544 observations of 356 participants. Each of the participants was exclusively assigned to one of ten treatments and made 24 subsequent decisions. Participants took the role of quantity managers of ‘their’ firm and had to choose a quantity [0-100] in every of the 24 periods. The ESRC Centre for Competition Policy (CCP) at the University of East Anglia (UEA) undertakes interdisciplinary research into competition policy and regulation that has real-world policy relevance without compromising academic rigour. It prides itself on the interdisciplinary nature of the research and the members are drawn from a range of disciplines, including economics, law, business and political science. The Centre was established in September 2004, building on the pre-existing Centre for Competition and Regulation (CCR), with a grant from the ESRC (Economic and Social Research Council). It currently boasts a total of 26 faculty members (including the Director and a Political Science Mentor), 4 full- and part-time researchers and 23 PhD students.